2002
DOI: 10.1530/eje.0.1470387
|View full text |Cite
|
Sign up to set email alerts
|

Development of an experimental ovarian tumor: immunocytochemical analysis

Abstract: Objective: The aim of the present work was to study whether immunocytochemical parameters present in the normal ovary were altered after tumor development under high gonadotropin levels. Methods: Ovarian tumors (luteoma): castrated female rats had an ovary grafted into the spleen; tumors were left to develop for 1, 2, 3 or 7 months. The presence of apoptotic cells (TUNEL method) and the expression of proliferating cell nuclear antigen (PCNA), gap junction protein (Cx43), steroidogenic acute regulatory protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The histological analysis showed that 86% of the tumors presented highly luteinized tissue, whereas II % showed granulosa cell predominance (Table II). No signs of corpora lutea involution were observed, in agreement with lack of TUNEL-positive cell detection in these tumors (30). Immunosuppressor treatments did not alter tumor histology, and no signs of malign transformation were observed.…”
Section: Discussionsupporting
confidence: 80%
“…The histological analysis showed that 86% of the tumors presented highly luteinized tissue, whereas II % showed granulosa cell predominance (Table II). No signs of corpora lutea involution were observed, in agreement with lack of TUNEL-positive cell detection in these tumors (30). Immunosuppressor treatments did not alter tumor histology, and no signs of malign transformation were observed.…”
Section: Discussionsupporting
confidence: 80%
“…The genes overexpressed in 'ovarian-type' stroma included sex hormone-related genes such as STAR and ESR1. The STAR protein, by enhancing the metabolism of cholesterol into pregnenolone, has a key role in steroid hormone synthesis, and is responsible for the transfer of cholesterol from the outer mitochondrial membrane to the inner mitochondrial membrane where it is cleaved to pregnenolone (Sorianello et al, 2002). In the normal ovary, STAR is expressed in luteinized follicles and in theca cells (Sorianello et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The STAR protein, by enhancing the metabolism of cholesterol into pregnenolone, has a key role in steroid hormone synthesis, and is responsible for the transfer of cholesterol from the outer mitochondrial membrane to the inner mitochondrial membrane where it is cleaved to pregnenolone (Sorianello et al, 2002). In the normal ovary, STAR is expressed in luteinized follicles and in theca cells (Sorianello et al, 2002). We observed overexpression of STAR transcript in 'ovarian-type' stroma, although other genes involved in progesterone and androgen biosynthesis were expressed at low levels.…”
Section: Discussionmentioning
confidence: 99%
“…According to the oligonucleotide microarray analysis on MCN, the over‐expression of several genes involved in estrogen metabolism, including steroidogenic acute regulatory (STAR) protein and estrogen receptor 1 (ESR1) genes , was observed in the ovarian‐type stroma (Table 1). The STAR protein, by enhancing the metabolism of cholesterol into pregnenolone, has a key role in steroid hormone synthesis, and is responsible for the transfer of cholesterol from the outer mitochondrial membrane to the inner mitochondrial membrane, where it is cleaved to pregnenolone . In the normal ovary, STAR is expressed in luteinized follicles and in theca cells.…”
Section: Molecular Genetics Of Mcnsmentioning
confidence: 99%
“…9 The STAR protein, by enhancing the metabolism of cholesterol into pregnenolone, has a key role in steroid hormone synthesis, and is responsible for the transfer of cholesterol from the outer mitochondrial membrane to the inner mitochondrial membrane, where it is cleaved to pregnenolone. 20 In the normal ovary, STAR is expressed in luteinized follicles and in theca cells. Ishiguro et al 21 found the expression of two steroidogenic enzymes, 3 beta-hydroxysteroid dehydrogenase (3 beta-HSD) and 17 alpha-hydroxylase (17 alpha H) in the ovarian-type stroma of pancreatic MCNs.…”
Section: Ovarian-type Stromamentioning
confidence: 99%